Kebijakan Hukum Pemerintah Dalam Melindungi Warga Negara Terkait Penyebaran Virus Covid-19 - Catur Hendro Martono; Anggraeni Endah Kusumaningrum (Badan Penerbit STIEPARI Press, 2022)
Health as a human right must be realized in the form of providing various health efforts to the entire community through the implementation of quality and affordable health development for the community. Law Number 36 of 2009 concerning Health, implies that every individual, family and community has the right to obtain protection for their health, and the state is responsible for regulating the fulfillment of the right to a healthy life for its population, including for the poor and underprivileged. This study uses a normative juridical approach with qualitative research analysis. The program to control the spread of the corona disease, managed by the government and the community, is an integrated policy to prevent transmission of the corona virus and improve the quality of life of citizens. Based on Law Number 36 of 2009 concerning health that every activity in an effort to maintain and improve the highest public health status is carried out based on non-discriminatory, participatory and sustainable principles.